New south american species of piperaceae (1953)
Piper ripagaudens / Piper Barkleyi Yuncker n. sp. / Piper Araquei Yuncker n. sp. / Piper longimucronatum Yuncker n. sp. / Piper virgatum Yuncker n. sp. / Piper scobinifolium Yuncker n. sp. / Piper pseudoarmatum Yuncker n. sp. / Piper criniovarium Yuncker n. sp. / Piper echinovarium Yuncker n. sp. / Piper taboganum C. DC. var. rugosum Yuncker n. var. / Trianaeopiper Haughtii Yuncker n. sp. / Peperomia persuculenta Yuncker n. sp. / Peperomia glanduligera Yuncker n. sp. / Peperomia glanduIigera var. villosissima Yuncker  n. var. / Peperomia Philipsonii Yuncker n. sp.